Seinfeld. Season 9 [videorecording (DVD)] - West, Howard; Shapiro, George; Ackerman, Andy; Kaiser, Tim; Greenberg, Suzy Mamann; Seinfeld, Jerry; Louis-Dreyfus, Julia; Richards, Michael, 1949-; Alexander, Jason, 1959-; David, Larry (Sony Pictures Home Entertainment, 2007)
Continuing the misadventures of these neurotic New York friends, Kramer finds out the amazing unknown uses of butter, George decides to associate food and television with his love life, Elaine borrows Kramer's meat slicer to feed a cat, and more.